O ENSINO DA EDUCAÇÃO FÍSICA E AS RELAÇÕES DE GÊNERO: REFLEXÕES DE UMA EDUCAÇÃO PARA A DIFERENÇA - Tatiana Roberta Medeiros (2023)
Gender studies have advanced in the contemporary context, thus intensifying discussions about public policies involving this theme. In this sense, this research proposal is justified by problematizing gender constructions within the school space and discussing how genders and their connections intersect in this context. In this aspect, the study's main objective is to investigate how teachers, who work in the final years of elementary education in the state network of Resende (RJ) and the municipal network of Quatis (RJ), develop content and proposals that address historical differences in gender formations. As specific objectives, the research aimed to provide a discussion on gender relations in Physical Education classes, analyze the process of differentiation through gender relations in Physical Education classes, and shed light on issues concerning the approach and possibilities of implementing a culturally focused Physical Education curriculum addressing gender issues. Through a qualitative investigation, data production in the field was carried out through semi-structured interviews with teachers working in the final years of primary education in the public state network of Resende/RJ and the public municipal network of Quatis/RJ. A total of 13 male teachers participated in the field study, and the interviews took place both remotely and in person. The analysis of the discourse was guided by contributions from post-critical studies. Upon examining the interlocutors' profiles, it was observed that the majority belong to the middle class, are of Black ethnicity, profess Christianity, and only one has a disability. Furthermore, considering gender as an analytical framework, we aim to reflect upon and inquire into how this concept is employed and mobilized by teachers in their pedagogical practice. Many of them question this concept only when it arises in conflicts during the class, while others prefer not to discuss this topic. Despite the efforts of some teachers to propose content that deviates from a traditional curriculum, the majority adhere to discourses rooted in biological aspects, which they use to justify the creation of traditional content in their pedagogical practices. It was noticed that the content proposed by these teachers is often marked by gendered representations that normalize the femininities and masculinities of the students. Additionally, we also perceive that, in the perspectives of the teachers in this study, working with mixed-gender groups would already be sufficient to achieve equality and respect for differences among students. We have observed that the masculinities of the teachers are constructed, leading to power struggles and dynamics of subordination through linguistic, discursive, and symbolic processes, mediated by social markers of difference. In this aspect, we perceive teachers who tend to adhere to a hegemonic approach, and there are also those who blur boundaries, moving towards plural masculinities. Lastly, even though the teachers did not explicitly mention the curriculum from a cultural perspective, we have found expressions that enable curriculum proposals of topics and content that align with this approach. Key-Words: Curriculum, Gender, Difference, School Physical Education.